THE MEDIATOR ROLE OF CRITICAL THINKING DISPOSITION IN THE EFFECT OF EMOTIONAL INTELLIGENCE AND GENERAL SELF-EFFICACY ON ATTITUDES TOWARDS LEARNING: A STUDY IN UNIVERSITY STUDENTS (Third Sector Social Economic Review, 2022)
The aim of this study is to determine the mediating role of critical thinking disposition in the effect of emotional intelligence and general self-efficacy on attitudes towards learning. Associate and undergraduate students studying at Yozgat Bozok University in the 2021-2022 academic year participated in the study, which was planned in a quantitative research design. Convenience sampling method was chosen in the research, and questionnaires were collected through online platforms with 414 students who agreed to participate in the study. The analysis of the collected data was analyzed through SPSS 22.00 and SPSS AMOS 24.00 programs. In the study, which was analyzed by establishing a structural equation model regarding the effects between variables, it was determined that emotional intelligence had a positive and significant effect on the attitude towards learning. Likewise, it was concluded that general self-efficacy had a positive and significant effect on the attitude towards learning. However, since emotional intelligence and general self-efficacy did not have a significant effect on critical thinking disposition, the mediation condition could not be met. Therefore, critical thinking disposition does not have a mediating role in the effect of emotional intelligence and general self-efficacy on attitudes towards learning. This study on university students is expected to contribute to the literature.
Keywords: Emotional Intelligence; General Self-Efficacy; Attitude to Learning; Critical Thinking Disposition